Macrobrachium pentazona, a new freshwater palaemonid prawn (Decapoda: Caridea: Palaemoindae) from Guangdong Province, China - He, Shun-Lian; Gao, Jie; Guo, Zhao-Liang (Zootaxa, 2009)
Macrobrachium pentazona, a new freshwater palaemonid prawn is described and is illustrated on the base of three specimens collected from a Beijiang river, near Qingyuan City, Guangdong Province, southern China. It can be distinguished from its congeners by a combination of characters that include the rostral formula; the segmental ratios and spination, the arrangement of teeth on the cutting edge of the fingers of the second pereiopod; the segmental ratios of third pereiopod; the wide scaphocerite; the small uropodal diaeresis spine; and with a regular striking colour pattern.